Teaching mathematics with interactive motion infographics created with GeoGebra - Giakati, Ioanna; Syropoulos, Apostolos; Tatsiou, Eleni (LUMAT-B: International Journal on Math, Science and Technology Education, 2022)
Teaching mathematics to middle-school pupils is always quite challenging. One has to introduce pupils to formal thinking and teach them the importance of this kind of thinking. Naturally, any tool that can assist the work of a teacher is more than welcome. GeoGebra is a tool that has been created by a mathematician for math teachers. This tool has the ability to create interactive motion infographics that can be used in a classroom. Creating such motion infographics is not particularly difficult but of course designing them is quite demanding, therefore, we first explain how one can create interactive motion infographics with GeoGebra and then we briefly discuss what one should have on her mind before starting to design such motion infographics. The ideas presented are by no means exhaustive; instead they can serve as a starting point for the development of a theory for the design of motion infographics for mathematics education.